Pengembangan Media Pembelajaran Smart Box di Kelas VII UPTD SMP Negeri 1 Kota Gunungsitoli - Seofeto, Ayu Irani Oktavianti; Ndruru, Mastawati; Bawamenewi, Arozatulo; Waruru, Lestari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop Smart Box learning media for the Indonesian language subject, specifically on official letter material for Grade VII at UPTD SMP Negeri 1 Gunungsitoli. The method used in this study is research and development (R&D). The learning media developed uses the 4D model, which consists of four main stages: define, design, develop, and disseminate. The results of the study show that the learning media developed has undergone a validation process by three experts, namely a material expert, a language expert, and a design expert. The validation results indicate that the material expert gave a score of 75% in the